If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + -4 = -2 + 16 Reorder the terms: -4 + 3x = -2 + 16 Combine like terms: -2 + 16 = 14 -4 + 3x = 14 Solving -4 + 3x = 14 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '4' to each side of the equation. -4 + 4 + 3x = 14 + 4 Combine like terms: -4 + 4 = 0 0 + 3x = 14 + 4 3x = 14 + 4 Combine like terms: 14 + 4 = 18 3x = 18 Divide each side by '3'. x = 6 Simplifying x = 6
| 1/x-x/5=0 | | -19x-57= | | 2+5x-3x+4= | | 20=2x+16 | | 3/2(2x-4)=x-2 | | -48x+96= | | 8b-25=7(3b-2)-2b | | f(x)=6x^2+5x-6 | | 2x+10+3(6x+10)= | | 2(4w-6)=32 | | 10(d+3)-(-9x-4)=x-5+3 | | 2x^9-2x=0 | | 18+6y=12x | | 9x+0.46y-15x-4.24y= | | -6times+5=17 | | -8(6x+10)= | | 3x-0.03y+2x+5.5y= | | V/2=3.2 | | log(x)=log(6)+log(x-1) | | 2(h+1)=13 | | 8/4-5i | | 45x+5x=7x-15 | | x^2t+5y=3z | | -5(-3)-3(-3)= | | 2t+35=70 | | h=-3t^2 | | 3xy+5zt=2 | | 8x-6(4x+9)= | | 60+50.45=57.97 | | 7x^2+2y^2=10 | | .5x-1= | | 1/x-5=1/4 |